Systematic review of the diagnosis of scabies in therapeutic trials. (29th May 2017) - Thompson, M. J.; Engelman, D.; Gholam, K.; Fuller, L. C.; Steer, A. C.
Summary: Human scabies (infestation with the mite Sarcoptes scabiei var hominis ) causes a significant disease burden worldwide, yet there are no agreed diagnostic guidelines. We aimed to determine whether a consistent approach to diagnosing scabies has been used for published scabies therapeutic trials. The data sources used were the MEDLINE, Embase and Cochrane databases, from 1946 to 29 August 2013. Eligible studies were trials of therapeutic interventions against scabies in human subjects, published in English, enrolling patients with scabies, and using various therapeutic interventions. Language was a limitation of this study as some relevant trials published in languages other than English may have been excluded. Each study was reviewed by two independent authors, who assessed the clinical examination and testing approaches used for scabies diagnosis in the included studies. We found that of 71 included trials, 40 (56%) specified which clinical findings were used for diagnosis, which were predominantly rash, rash distribution, pruritus and mite burrows. Parasitological testing was used in 63% of trials ( n = 45) and was used more frequently in clinic‐based than in field studies. Nearly one‐quarter of trials (24%, n = 17) did not define the diagnostic method used. Overall, the diagnostic approaches were poorly described, prohibiting accurate comparison of existing studies. This review further supports the need for consensus diagnostic guidelines for scabies. Abstract : Clickhere for the corresponding questions to this CME article.